Kebijakan Berdimensi Syariah dalam Sistem Partai Politik Islam - A. Bakir Ihsan (AHKAM : Jurnal Ilmu Syariah, 2017)
The study of Sharia-compliant policy tends to be seen only in the aspect of output, while processes and mechanisms are not much attention. Sharia-compliant policy is actually born from Islamic processes and systems that provide a conducive space for its emergence. The existence of Islamic political parties as the forces involved in legislation is very important toexamine to see the aspects of sharia in the process of making it. Through this qualitative approach, this paper dissects the mechanism of policy formulation applied by Islamic political parties, in this case the Development Unity Party(PPP) to see the relation between process and output. DOI: 10.15408/ajis.v17i2.6234